Psycho-Emotional State of Students with Special Educational Learning Needs - Nurgul, Toxanbaeva; Almukhambetova, Bibigul; Madaliyeva, Zabira; Nazirash, Zhubanazarova; Orazbekovna, Baimoldina Laura; Bakytkyzy, Toxanbayeva Nazgul (Journal of Intellectual Disability - Diagnosis and Treatment, 2018)
This article is devoted to the study of the psycho-emotional state of students with special educational needs in education. The primary objective of the study was to study the theoretical views of domestic and foreign researchers on the psycho-emotional state and manifestation of anxiety; to conduct a theoretical analysis of the relationship of stress and the learning process; to clarify the manifestation of anxiety among students with special educational needs of our University in the learning process. The hypothesis of the study was as follows: for students with special educational needs, the learning process is accompanied by a manifestation of anxiety and harms their psycho-emotional state. The results obtained in the course of the study led to the conclusion that students with special educational needs in the learning process involve a range of factors that determine the behavioural reactions of frustrating nature. And that is why, because of the mismatch of opportunities, priorities, there is an increase in the normative level of anxiety, which affects their overall psycho-emotional state.